Parental Attitude in Families Bringing up Preschoolers with Autism Spectrum Disorders - V.V. Kisova; I.A. Koneva (Moscow State University of Psychology and Education, 2022)
The article presents the results of a study of the parental position in families raising children with autism spectrum disorders. The experimental program for the study of the parental position includes valid and reliable questionnaires aimed at identifying family anxiety (Family Anxiety Analysis), parental attitudes (Parent Attitude Research Instrument), family relationships (Analysis of Family Relationships), attitudes towards the child's illness (Tool for Diagnosing of Attitudes Towards a Child's Illness). The study sample consists of 40 parents: 20 subjects raising preschoolers with autism spectrum disorders and 20 subjects raising normally developing children. The results of the study allow us to speak about the low productivity of the parental position in families with preschoolers with autism spectrum disorders. This expressed in hyperprotection and an indulgent parenting style, in a tendency to establish symbiotic relationships and an ambivalent emotional attitude, etc. Most parents with children with autism spectrum disorders need specially organized work to correct the parental position.